Pengaruh Brand Trust, Price, dan Brand Image Terhadap Loyalitas Pelanggan (Studi Kasus Pada Pelanggan Teh Poci di Kota Malang ) - Mauludi, Mokhammad Faiz; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to examine how brand trust, price, and brand image have an impact on customer loyalty among iced tea pot customers in Malang. Using multiple linear regression techniques, this study concentrates on explanatory research investigations with a quantitative approach. A sample of 75 participants was selected using the Malhotra formula. Data analysis was carried out through SPSS version 26 software which included tests of validity, reliability, normality, classical assumptions, hypotheses, and determination coefficients (R2). The results of the study show that simultaneously brand trust, price and brand image have a positive and significant influence on the loyalty of iced tea pot customers. Partially, the Brand Trust variable has a significant effect on customer loyalty, while the Price variable does not have a significant influence. And also the brand image variable does not have a significant influence on customer loyalty. This research has important implications for companies in optimizing marketing strategies, especially in strengthening brand image and increasing the strength of brand trust as the main factor affecting customer loyalty. Keywords: Brand Trust, Price, Brand Image, Customer Loyalty